KHAZANAH PERISTILAHAN MUSIM DURIAN JERAH MASYARAKAT MELAYU SUKADANA - Syahefti, Dela; Patriantoro, Patriantoro; SyahranI, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractDurian Jerah season in Sukadana Malayan Society is a form of hereditary cultural activity. Sukadana Malayan Terminologies are also related to their life vision in seeing things that happened in life. Therefore, the terminologies of Durian Jerah Season in Sukadana Malayan Society are considered of having lifetime moral values (classic). The terminologies in Sukadana Malayan Society usually considered as a certain thing or event. In this research, Terminologies of Durian Jerah Season in Sukadana Malayan Society are determined by the form and category, lexical meaning and cultural meaning.  The methods used in this research are data collecting method and data analyzing method. The approaches used in this research are structural, semantic, and etnolinguistic approach. The source of data in this research is the terminologies of Durian Jerah Season spoken by the native speaker. The techniques in this research are inducement, direct interview, and note and record techniques. The tools in collecting data is the researcher as key instrument with notes and sound recorder. Based on the research result Terminologies of Durian Jerah Season consist of three terms: monomorphism for 33 terms, polymorphism for 2 terms, and frases for 82 terms. Overall, the plants terms consist of 11 lexical meanings and 123 cultural meanings, 2 myths, 5 prohibitons, and 6 spoken literary.       Keywords: terminologies, durian jerah season, Sukadana Malayan Society